The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00415-016-8080-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the burden of caregiving in Duchenne muscular dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is a rare pediatric neuromuscular disease associated with progressive muscle degeneration and extensive care needs. Our objective was to estimate the caregiver burden associated with DMD. We made cross-sectional assessments of caregiver health-related quality of life (HRQL) and burden using the EuroQol EQ-5D, a Visual Analogue Scale (VAS), the SF-12 Health Survey, and the Zarit Caregiver Burden Interview (ZBI) administered online. Results were stratified by disease stage (earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
153
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(172 citation statements)
references
References 38 publications
(45 reference statements)
12
153
1
6
Order By: Relevance
“…The two studies that specifically measured depression did not find clinically significantly symptoms, but four of their ten NIV users had previously sought help for psychological problems 50 . The interplay between family and individual mental health alluded to by Read et al 50 is confirmed in the recent publication by Landfeldt et al 63 , who found that individuals with DMD whose parents self-reported depression and anxiety were at higher risk of mental health issues. It is concerning that up to 70% of parents were recorded as experiencing anxiety and depression 63 .…”
Section: Psychosocial Domains Of Qol -Mental Health and Emotional Welmentioning
confidence: 82%
See 1 more Smart Citation
“…The two studies that specifically measured depression did not find clinically significantly symptoms, but four of their ten NIV users had previously sought help for psychological problems 50 . The interplay between family and individual mental health alluded to by Read et al 50 is confirmed in the recent publication by Landfeldt et al 63 , who found that individuals with DMD whose parents self-reported depression and anxiety were at higher risk of mental health issues. It is concerning that up to 70% of parents were recorded as experiencing anxiety and depression 63 .…”
Section: Psychosocial Domains Of Qol -Mental Health and Emotional Welmentioning
confidence: 82%
“…The interplay between family and individual mental health alluded to by Read et al 50 is confirmed in the recent publication by Landfeldt et al 63 , who found that individuals with DMD whose parents self-reported depression and anxiety were at higher risk of mental health issues. It is concerning that up to 70% of parents were recorded as experiencing anxiety and depression 63 . Hence, whilst high emotional functioning scores in possibly emotionally well-supported populations indicate a resilience amongst youth with NMD 49,64 , more careful measurement of mental health and emotional wellbeing is needed to identify times of vulnerability both for themselves and their families.…”
Section: Psychosocial Domains Of Qol -Mental Health and Emotional Welmentioning
confidence: 82%
“…25 Nonetheless, the review found a substantial economic burden of rare diseases, including both direct costs (e.g., treatment) and indirect costs-in particular, productivity losses incurred by informal caregivers. Similarly, a recent study 24 of the burden of Duchenne muscular dystrophy, an X-linked neuromuscular disorder, reported mean annual direct per-patient costs of between $23,000 and $55,000. This study also measured indirect and informal care costs, finding that they accounted for between 18 and 43% of total costs.…”
Section: Discussionmentioning
confidence: 96%
“…[24][25][26][27] Despite this, relatively little is known about their associated economic burden beyond direct medical costs. 24,25 However, a more comprehensive understanding of disease burden, including nonclinical burdens such as financial impact, is required to personalize disease management according to families' needs. 28 Identification of both direct and indirect costs associated with chronic genetic conditions is of further importance to policymakers in order to develop sustainable and patient-centered health policy options for families affected by rare diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation